Very low particle matter mass measurements from light-duty vehicles. (March 2018) - Xue, Jian; Johnson, Kent; Durbin, Tom; Russell, Robert; Pham, Liem; Miller, Wayne; Swanson, Jacob; Kittelson, David; Jung, Heejung
Abstract: Recently, there are discussions about whether current sampling and measurement practices for the regulated gravimetric PM measurement are sufficiently accurate in quantifying PM at the proposed 3 and 1 mg/mi emission standards for light-duty vehicles. In this study, a series of modifications were made to the existing gravimetric PM measurement method, aiming to preserve the integrity of the method while increasing the robustness and decreasing the testing variability. The experiments were conducted with a Higher (~2 mg/mile) and a Lower (0.1–0.2 mg/mile) PM Source Vehicle over the Federal Test Procedure (FTP) and US06 cycles, providing PM emissions with various solid/semi-volatile compositions and size distributions. The results showed the suggested modifications, i.e., increased filter face velocities (from 100 to 150 cm/s) and combined filters (single filter vs. 3/4 filters), could increase the collected filter mass without introducing statistically significant differences in the measured PM mass emission rates. No statistically significant improvements were seen in the measurement variability with the Higher PM Source Vehicle. For the Lower PM Source Vehicle; however, the 4-phase cumulative filter showed a statistically significant reduction in PM mass measurement variability, while not impacting the measured PM mass emissions, but these improvements must be weighed against the increased testing costs/time required for the longer test time. Graphical abstract: Highlights: To modify gravimetric method for low PM mass emission from modern vehicles. 4-phase combined filter method significantly reduced PM mass measurement variability. The improvements should be weighed against the increased testing costs/time.